Evaluating the probability of avoiding disease‐related extinctions of Panamanian amphibians through captive breeding programs. (4th January 2016) - Gratwicke, B.; Ross, H.; Batista, A.; Chaves, G.; Crawford, A. J.; Elizondo, L.; Estrada, A.; Evans, M.; Garelle, D.; Guerrel, J.; Hertz, A.; Hughey, M.; et al.
Abstract: Amphibians around the world are declining from threats that cannot currently be mitigated, making it impossible to safeguard some species in their natural habitats. Amphibians in the mountainous neotropics are one example where severe disease‐related declines prompted calls for the establishment of captive assurance colonies to avoid extinctions. We surveyed experts in Panamanian amphibians to determine the probability of avoiding chytridiomycosis‐related extinctions using captive breeding programs. We ranked Panamanian amphibian species by perceived susceptibility to chytridiomycosis, then calculated the likelihood of avoiding extinction as the product of three probabilities, which include (1) finding sufficient founder animals, (2) successfully breeding these species in captivity and (3) becoming extinct in the wild. The likelihood of finding enough animals to create a captive founding population was low for many rare species, especially for salamanders and caecilians. It was also low for frogs which were once regularly encountered, but have already disappeared including Atelopus chiriquiensis, Craugastor emcelae, C. obesus, C. punctariolus, C. rhyacobatrachus, Ecnomiohyla rabborum, Isthmohyla calypsa and Oophaga speciosa . Our results indicate that captive breeding could improve the odds of avoiding extinction for species that have severely declined or are likely to decline due to chytridiomycosis including Atelopus certus, A. glyphus, A. limosus, A. varius, A. zeteki, Anotheca spinosa, Gastrotheca cornuta, Agalychnis lemur and Hemiphractus fasciatus . Priority species that experts predicted were highly susceptible to chytridiomycosis that might also benefit from ex situ management include Craugastor tabasarae, C. azueroensis, C. evanesco, Strabomantis bufoniformis and Colostethus panamansis . In spite of high levels of uncertainty, this expert assessment approach allowed us to refine our priorities for captive amphibian programs in Panama and identify priority conservation actions with a clearer understanding of the probability of success. Abstract : We surveyed amphibian experts to determine the probability of avoiding chytridiomycosis‐related extinctions of Panamanian species using captive breeding programs. We found that the following species already represented in captive collections had the highest chances of avoiding extinction: Atelopus zeteki (top left), A. varius (top middle), A. limosus (top right), A. certus (second row left), A. glyphus (second row right), Agalychnis lemur, (third row left) Hemiphractus fasciatus (third row right), Gastrotheca cornuta (bottom left) and Anotheca spinosa (bottom right). Other species that experts predicted were highly susceptible to chytridiomycosis that might also benefit from ex situ management include Craugastor tabasarae, C. azueroensis, C. evanesco, Strabomantis bufoniformis and Colostethus panamansis .